Glycogen Storage Diseases Presenting as Hypertrophic Cardiomyopathy - Arad, Michael; Maron, Barry J; Gorham, Joshua M; Johnson, Walter H; Saul, J. Philip; Perez-Atayde, Antonio R; Spirito, Paolo; Wright, Gregory B; Kanter, Ronald J; Seidman, J.G; Seidman, Christine E (The New England journal of medicine, 2005)
Hypertrophic cardiomyopathy is usually caused by mutations in sarcomere proteins, but in some patients such mutations are not found. This study identified mutations in genes encoding enzymes involved in glycogen metabolism as causes of hypertrophic cardiomyopathy. Thus, glycogen storage diseases may sometimes present as hypertrophic cardiomyopathy, owing to accumulation of glycogen-filled vacuoles in myocytes. This study identified mutations in genes encoding enzymes involved in glycogen metabolism as causes of hypertrophic cardiomyopathy. Hypertrophic cardiomyopathy, an autosomal dominant disorder associated with increased morbidity and premature mortality, is traditionally diagnosed on the basis of increased cardiac mass with histopathological findings of myocyte enlargement, myocyte disarray, and cardiac fibrosis. 1 – 3 However, given the availability of sophisticated noninvasive imaging techniques, an echocardiographic demonstration of unexplained left ventricular hypertrophy constitutes the current basis for a diagnosis of hypertrophic cardiomyopathy. 3 Echocardiography has shown that there is considerable diversity in the manifestations of hypertrophic cardiomyopathy, including variable age at onset, from early childhood to late adulthood, and severity of left ventricular hypertrophy. Left ventricular wall thickness in hypertrophic cardiomyopathy . . .